2012
DOI: 10.1378/chest.11-0362
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Improve Communication About End-of-Life Care Among Patients With COPD

Abstract: In the United States, COPD is the leading cause of respiratory-related deaths and is the third overall leading cause of death. 1 COPD often causes a progressive decline in quality of life and places patients at risk for acute respiratory failure that can require intensive care. Currently, there is no consensus on when discussions about preferences for end-oflife care should take place with these patients. The American Thoracic Society/European Respiratory Society guidelines on COPD recommend these discussions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 147 publications
(187 citation statements)
references
References 28 publications
3
184
0
Order By: Relevance
“…When end-of-life discussions occur in patients with COPD, most occur during an acute exacerbation rather than a more stable state of their disease, and the skill of the providers leading the discussion is commonly inadequate [243][244][245]. Similarly, palliative care is often not addressed or inadequately addressed in patients with COPD, permitting symptoms whose mitigation or elimination would provide comfort to patients with COPD, such as dyspnoea, cough, pain and fatigue, and less commonly poor sleep quality, depression and anxiety [246,247].…”
Section: End-of-life Carementioning
confidence: 99%
“…When end-of-life discussions occur in patients with COPD, most occur during an acute exacerbation rather than a more stable state of their disease, and the skill of the providers leading the discussion is commonly inadequate [243][244][245]. Similarly, palliative care is often not addressed or inadequately addressed in patients with COPD, permitting symptoms whose mitigation or elimination would provide comfort to patients with COPD, such as dyspnoea, cough, pain and fatigue, and less commonly poor sleep quality, depression and anxiety [246,247].…”
Section: End-of-life Carementioning
confidence: 99%
“…17 out of 37 papers highlighted that a variable percentage of COPD patients had discussed palliative care topics, this ranged from 0% to 56%, [5,19,21,24,25,29,30,[35][36][37][38][39][40][41][42][43][44]. Within this group, the majority (n=9), reported rates of discussion ⩽30% of patients [19,29,30,[35][36][37][38][39]43]. This information was generated from papers including qualitative and quantitative studies with moderate and high quality, papers which compared COPD patients and patients with other diseases and narrative reviews.…”
Section: Frequency Of Discussionmentioning
confidence: 99%
“…Quality of communication appeared to remain poor as patients approached their end of lives, even after the use of interventions to improve the frequency and quality of these discussions [36,39]. Interventional studies demonstrated potential for improvement the quality of conversations, but only in two domains: patients' feelings about deterioration and spiritual beliefs [36,39].…”
Section: Quality Of Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Patients who met the GOLD (Global Initiative for Obstructive Lung Disease) criteria for COPD were enrolled between November 2004 and December 2007. The protocol was approved by the institutional review board of the University of Washington and the Veterans Affairs Puget Sound Health Care System (approval number 01378).…”
Section: Participantsmentioning
confidence: 99%